Mismatch negativity of preschool children at risk of developing mental health problems - Toshiya Aoi; Takashi X. Fujisawa; Shota Nishitani; Akemi Tomoda (Wiley, 2021)
Abstract This study examined the relationship between mismatch negativity (MMN) during the passive oddball task and clinical assessment using a behavioral scale in nonclinical preschool children to identify neurobiological endophenotypes associated with the risk of developing mental health problems. We assessed the risk of developing mental health problems in preschool children using the Strengths and Difficulties Questionnaire, which is used worldwide as a behavior‐based screening tool for assessing mental health risks, and examined its relevance to amplitude and latency MMN. As a result, we found that children at a higher risk of mental health problems had smaller MMN amplitudes than those at lower risk. It was also found that MMN amplitude was negatively correlated with the assessed higher risk of mental health problems. Although it is not clear what neural mechanisms underlie the functional association between MMN and risk of mental health problems in preschool children, the findings of this study indicate that there is an involvement of individual differences in auditory processing in childhood mental health problems. The findings suggest that such neurological changes may be prodromal symptoms of the onset of psychiatric disorders and applicable as endophenotypic markers for the early detection of various psychiatric disorders.